An increasing trend and impact of non communicable diseases in Vanuatu - Wesley Donald (Berita Kedokteran Masyarakat (BKM), 2018)
Non Communicable Diseases (NCDs) continue to elevate in the western pacific regions, including Vanuatu. Much efforts have been made in reducing the disease burden, however the challenges remains due to certain sociocultural behaviours, globalization, and urbanization which promotes unhealthy lifestyles such as eating lifestyles (unhealthy diet), physical inactivity, harmful use of alcohol and tobacco use. All these contributing factors tends to give rise to common risks for the intermediate factors such as raised in blood pressure, raised in the level of glucose in the blood, the unhealthy lipid profiles, and obesity.Comparing this disease in low-income countries and high-income countries it seem that the rate of NDC are higher in low-income countries, more specifically the countries in the western pacific regions. Even that there are few South East Asian countries such Vietnam, Malaysia, Philippines, and Cambodia which were also regarded as having high mortality rates of NCD (1). According to the profile in 2008 it was estimated that it's the western pacific region that has more of the effect, showing more than a quarter of the 36 million deaths were due to NCD alone.Furthermore it continue to states that the trend will continue to increase by 15% between 2010 and 2020, meaning an estimation (from baseline) from an elevation of up to 44 million deaths will be cause by NCD alone (1). And if we divide the figures up it will then show that the highest proportion will be from the Western Pacific regions, of 12.3 million of deaths, while South-East Asian regions on the other hand is estimated to reach 10.4 million. This is also supported by a report on economic-cost of NCD in the Pacific Island countries which states that NCD is already a challenge in the Pacific, leading to account for 70% or more of the deaths. And the most common cause is of cardiovascular disease, which accounts for between 29% and 38% of death from all other causes (2). In Vanuatu NCD is in the top 10 disease agenda due to fast escalating trend, and similarly are Cardiovascular diseases, including diabetes and hypertension. According to the reported it was estimated that 18% of deaths were due to circulatory heart diseases (7).Another study been conducted in 2008 showed a record of 0.5% and 0.3% deaths were respectively caused by NCD in male and female. The current daily tobacco smoking as a form of behavioural risk factor constitute of 12.3%, where 21.3% in male and 3.1% in female. Additionally from the study record it showed that males are more risks than female in having high blood pressure above normal. This is supported by showing 44.5% of males in the study have raised blood pressure, while female on contrary have 39.1% raised blood pressure. Other contributing factor in the metabolic risks factors are overweight and obesity. From the study it showed that 21% of both male and female are overweight, while 34.2% is of obesity (3).From the findings we have to know that there are unprecedented changes in our environment – cultural, economic, physical, political and social – pose new risks and threats to health. And from most reports and future focus it is predicted that NCD will continue to elevate globally, whether it is urbanization and the built environment, severe air pollution, climate change, unregulated marketing of tobacco and other harmful food products, or easy access to nutrient-poor and calorie dense food (4). In some countries, for instance Vanuatu still accepts more imported and processed food and is predicted to upscale further should the climate conditions such as the current El Nino continue to place threats on garden crops. There is additionally a weak monitoring on food regulations on imported food products and where most labelling are in languages. Lack of proper laboratory analysis of the content against the labelling is another contributing factor. Thus it is imperative that leaders in both Government and related Non-Government Organizations (NGOs) find innovative solutions to complex health challenges in ever-changing common practices and environments. Only then will the population be safe and healthy from the disease. On the other hand we have to understand that at each developmental stage of life, human beings exhibit different vulnerabilities and are exposed to different risks, placing them more vulnerable to contracting those diseases.According to WHO report in 2008 on prevention and control of non-communicable diseases (Annex 1-B) (5), in year 2000 the WHO's Member States adopted a global strategy for prevention and control of NCDs during the fifty-third World Health Assembly. The Global Strategy on Diet, Physical Activity and Health was endorsed in 2002. In 2003, the WHO launched the Framework Convention on Tobacco Control, and this treaty came into force in 2005. Even that in 2008 the Member States endorsed the Action Plan for the Global Strategy for the Prevention and Control of non-communicable Diseases at the Sixty-first World Health Assembly. And the Regional Committee for the Western Pacific called for action to combat non-communicable diseases and their related risk factors in specific resolutions. There are also various regional action plans related to NCD prevention and control (e.g. Regional Plan for Integrated Prevention and Control of Cardiovascular Diseases and Diabetes for the Western Pacific Region 1998–2003, Tobacco Free Initiative Regional Action Plans 2000–2004 and 2005–2009, Plan of Action 2006–2010 for the Western Pacific.Declaration on Diabetes, and the Regional Strategy to Reduce Alcohol-related Harm) were developed over the past decade, sharing a focus on policy and planning, surveillance, health promotion and clinical prevention. Furthermore WHO developed a Pacific Framework for the Prevention and Control of Non-communicable Diseases in 2007 to serve as a guide in addressing NCDs among Pacific island countries and areas, and this framework was adopted by the Secretariat of the Pacific Community (SPC). Augmenting these action plans and frameworks is a Region-wide interest and commitment to fostering health systems change, particularly in relation to the prevention and control of NCDs. In November 2007, the WHO-supported meeting on "Strengthening Health Systems to Improve Chronic Disease Prevention and Control" culminated in a set of recommendations for reducing the health burden from non-communicable diseases through health systems improvements. The Western Pacific Regional Action Plan for NCDs is a collaborative effort by the WHO Regional Office for the Western Pacific and Member States to establish a shared vision and strategic actions to reduce the NCD burden (5).However despite of all these developed global and regional framework, strategies, planning, and action plans it is still recognized that countries still have less capacities and some are still at different stages of progress in the fight against non-communicable diseases. Therein it is suggested that more plenary discussions, consultations, and a support networking collaborations be established between the Government and private sectors, including the partners and associated stakeholders, and the affected communities. Moreover the Regional Action Plan also aims to operationalize the objectives of the Global Action Plan within the Western Pacific context, thereby adding value through concrete and relevant guidance. In other words the member states need to reconsider and rectify these further to be able to absorb perfectly into the country settings and the environmental contexts. Vanuatu on the other hand has also the capacity to address and respond to NCDs as it has its funding available for Cardiovascular diseases, NCD treatment for control, prevention and health promotion messages, and NCD surveillance and M&E. Additionally the health reporting system also includes information on screening of patients at health peripheries, NCD cause specific –morbidity, and the risks factors. Further to that the country has an integrated or topic-specific policy, programme, and action plan which is currently operational for these mentioned NCD diseases, including Alcohol, unhealthy diet, overweight, and obesity. Physical inactivity and Tobacco were other areas that the policy and action plan covers (1).Furthermore the member states need to strictly consider and implement WHO global NCD action plan which is a road map from 2013 to 2025 (6). In the road map are six global objectives that clearly states to make prevention and control of NCDs a priority, strengthening national capacities and leaderships, reduce modifiable risks factors, promote high-quality research, and finally is to monitor the impact and the trend of the disease. Additionally are nine major and more specific targets along the road map towards 2025. These are to be able to establish 80% availability of affordable technology and medicine to treat NCDs, ensuring that at least 50% of the patients receive preventive therapy for heart attacks and stroke, be able to pause the rise in diabetes and obesity, at least a 30% drop in sodium chloride (salt) intake, a 10% reduction in the harmful in the use of alcohol, to at least also receive 25% drop in premature death of people age 30-70 from cardiovascular diseases, cancers, diabetes, or chronic respiratory diseases, be able to reduce 10% in the prevalence of insufficient physical activity, reduce by 30% in tobacco use, and finally is to drop by 20% in the prevalence of high blood pressure (6). All these can be adopted and implemented strategically and effectively only when adequate resources such as adequate human resource, access to appropriate technology at all levels of implementations, adequate financial support, good working collaborations with partners and NGOs, including the communities, other associate stakeholders such as community leaders, and a very motivated and action-oriented personals are in place. Moreover is the health systems, political commitment, good network with shop entrepreneurs, and private sector that can contribute in the prevention and promotion of these mentioned health lifestyles.It is therefore strongly believed that unless all these are identified and notified then will there be some changes expected, and thus meet most of the target indicators as stated in the 2013-2025 target objectives.